2009
DOI: 10.2527/jas.2008-1496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing levels of dried corn distillers grains with solubles on growth performance, carcass characteristics, and meat quality of yearling heifers1

Abstract: Three hundred forty-seven crossbred heifers (330 +/- 11 kg initial BW) were used in a randomized complete block study to identify the optimal level of dried corn distillers grains with solubles (DGS) in flaked corn finishing diets. Fifty-four pens were used, with 9 pens per treatment and 6 to 7 heifers per pen. Finishing diets were steam-flaked corn-based and were fed once daily for 148 d. Dietary treatments consisted of 6 levels of DGS (0, 15, 30, 45, 60, and 75%, DM basis). Dry matter intake, ADG, and final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
75
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 24 publications
12
75
5
1
Order By: Relevance
“…It was hypothesized by Gunn et al (2014) that the lack of increase in BCS by feeding DDGS was due to a shift in location of fat deposition, where internal fat was deposited rather than subcutaneous fat. A change in location of fat metabolism is also supported by data from Depenbusch et al (2009) who observed a linear decrease in 12th rib fat along with a quadratic increase in internal fat when feedlot heifers were fed from 0% to 75% DDGS on a DM basis. It appears from data in the present experiment that the excess protein and fat in DDGS does not decrease subcutaneous fat stores (as measured by BCS) when it is fed during lactation, however, it is possible that fat deposition may have been altered internally.…”
Section: Resultsmentioning
confidence: 59%
“…It was hypothesized by Gunn et al (2014) that the lack of increase in BCS by feeding DDGS was due to a shift in location of fat deposition, where internal fat was deposited rather than subcutaneous fat. A change in location of fat metabolism is also supported by data from Depenbusch et al (2009) who observed a linear decrease in 12th rib fat along with a quadratic increase in internal fat when feedlot heifers were fed from 0% to 75% DDGS on a DM basis. It appears from data in the present experiment that the excess protein and fat in DDGS does not decrease subcutaneous fat stores (as measured by BCS) when it is fed during lactation, however, it is possible that fat deposition may have been altered internally.…”
Section: Resultsmentioning
confidence: 59%
“…There was no difference tenderness concentrations between treatments for any other aging and retail display period (data not presented). Segers et al (2011) reported that beef from cattle supplemented with 25% dried distillers plus solubles for 100 days was more tender than beef from cattle supplemented with soybean meal at 7 days of aging, and Depenbusch et al (2009) reported sensory overall tenderness ratings increased linearly as dietary level of distillers grains increased from 0% to 75%. Finally, Senaratne (2012) reported that beef from steers fed 30% WDGS tended (P < 0.10) to be more tender than beef from steers not fed a corn-only diet.…”
Section: Wbsf and Free Calcium Concentrationmentioning
confidence: 99%
“…Although many beef quality studies (Roeber et al 2005;Koger et al 2010;Mello et al 2012) on feeding distillers grains reported no differences in tenderness between control and treatments, a recent study (Senaratne 2012) revealed an intriguing phenomenon. Beef from steers fed 30% wet distillers grains plus solubles (WDGS) was more tender than beef from steers not fed WDGS, and this is not the first time that feeding distillers grains is reported to improve tenderness (Depenbusch et al 2009;Segers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of differing inclusion rates of DGS on aspects such as shelf life and tenderness of beef products have been evaluated (Depenbusch et al, 2009;Kroger et al, 2010), few reports on the effect of the S concentration of the diet on meat quality are available.…”
Section: Effects On Carcass and Meat Characteristicsmentioning
confidence: 99%